# How do you solve -5( - 2x + 3) = 15- 5x?

Sep 8, 2017

See a solution process below:

#### Explanation:

First, expand the terms in parenthesis by multiplying each term within the parenthesis by the term outside the parenthesis:

$\textcolor{red}{- 5} \left(- 2 x + 3\right) = 15 - 5 x$

$\left(\textcolor{red}{- 5} \times - 2 x\right) + \left(\textcolor{red}{- 5} \times 3\right) = 15 - 5 x$

$10 x + \left(- 15\right) = 15 - 5 x$

$10 x - 15 = 15 - 5 x$

Next, add $\textcolor{red}{15}$ and $\textcolor{b l u e}{5 x}$ to each side of the equation to isolate the $x$ term while keeping the equation balanced:

$10 x + \textcolor{b l u e}{5 x} - 15 + \textcolor{red}{15} = \textcolor{red}{15} + 15 - 5 x + \textcolor{b l u e}{5 x}$

$\left(10 + \textcolor{b l u e}{5}\right) x - 0 = 30 - 0$

$15 x = 30$

Now, divide each side of the equation by $\textcolor{red}{15}$ to solve for $x$ while keeping the equation balanced:

$\frac{15 x}{\textcolor{red}{15}} = \frac{30}{\textcolor{red}{15}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{15}}} x}{\cancel{\textcolor{red}{15}}} = 2$

$x = 2$